Current Techniques of Intravascular Imaging and Implantation of Bioresorbable Coronary Vascular Scaffolds (Stents) - I. E. Nikolaeva; I. G. Zagitov; I. V. Buzaev; R. Yu. Risberg (Креативная хирургия и онкология)
Introduction. The use of intravascular imaging techniques, in particular intravascular ultrasound, makes it possible to reduce the number of subsequent revascularisations. The method of optical coherence tomography (ОСТ), due to its high resolution accuracy, makes it possible to establish and assess the edge dissection, stent thrombosis, tissue prolapse, and strut fracture and malposition. This paper aims to assess the impact of routine use of OCT on long term outcomes in patients with scaffolds implanted.Materials and methods. 32 stenting procedures with the use of bioresorbable coronary intravascular scaffolds (Absorb, Abbot Vascular) were performed in 2014-2015 with subsequent visualisation and assessment with optical coherence tomography. In the control group (n=16) scaffolds were implanted without the use of OCT under traditional contrast enhanced X-ray imaging. The analysis of the combination of outcomes that included subsequent emergency revascularisation in the target artery, cardiac death, myocardial infarction and 12 months post-op OCT imaging data, served as the end.Results. The total of 55 BVS were implanted, 22 in the OCT group and 23 in control. Suboptimal results were registered in eight cases out of 16 in the OCT group (50%). These included: one dissection and atherosclerotic plaque prolapse — implantation of a second BVS and postdilatation, one eccentric stent expansion — a model for acute thrombosis, resolved with postdilatation, and stent underexpansion in the remaining six. Once the OCT revealed the intima dissection following predilatation; this was stabilised with the implantation of a second scaffold. The examination results at 12 months follow up established that there were 3.215 more scaffold restenoses in the control group.Conclusion. The cutting edge technique of intravascular revascularisation with bioresorbable coronary scaffolds requires careful preparation and intraoperative control. The results of our study support the use of intravascular imaging techniques as methods of choice for the assessment of the expansion, areas of dissection, thrombosis and scaffold eccentricity.